Adjuvant treatment with repetitive transcranial magnetic stimulation in freshly diagnosed alcohol-dependence syndrome patients from an industry: An outcome study - Anindya Kumar Gupta (Wolters Kluwer Medknow Publications, 2021)
Background: Studies have suggested that repetitive transcranial magnetic stimulation (rTMS) could be efficacious in the treatment of major depression and other psychiatric indications. Alcohol-dependence syndrome is difficult to treat, and the relapse rate is high, even following the standard treatment protocol. No study has been done so far in India for the use of rTMS as an adjuvant therapy in the relapse prevention of patients with alcohol-dependence syndrome. Hence, the current study is an open-label study to explore the same. Aim: The aim of this study was to study the feasibility of rTMS in alcohol-dependence syndrome patients, the side effects if any, and the number of relapses that they may suffer from vis-a-vis patients with standard treatment protocols. Materials and Methods: In a prospective, open-label study design, 100 freshly diagnosed cases of alcohol-dependence syndrome were included, and after suitable randomization, half of them were given adjuvant rTMS along with standard treatment and the rest received only standard treatment. The rates of relapse into drinking were compared for both groups. The data were compiled and analyzed with appropriate statistical methods. Results: Participants given adjuvant rTMS showed significantly less number of relapses into drinking compared to the control group on standard treatment for alcohol-dependence syndrome. Conclusion: In the present study, though the sample size is small, a significant change with this novel treatment has been found. Whether this change is maintained over a period of time is to be seen by other longitudinal studies.